A Qualitative Study on Foreign Language Teaching Anxiety - Hülya İpek (Anı Publishing, 2016)
Affective constructs such as motivation, self-esteem, and anxiety play an important role in learning a foreign language. Scholars have conducted many studies to find out how these constructs affect foreign language (FL) learning. They aimed to find out how anxiety affects language learning, the sources of anxiety in FL learners, and how to overcome this anxiety. Teachers were offered various strategies to lower their students' anxiety. Studies on Foreign Language (FL) anxiety mostly focused on the language learner. However, few studies investigated the anxiety experienced by teachers of English as a foreign language (EFL). This study aimed to investigate the factors that create anxiety in non-native EFL teachers while teaching the target language, English. Qualitative research design was used in this study. Data were collected through diaries and semi-structured interviews from 32 non-native EFL teachers. The data were analyzed manually using the content analysis technique. The results showed in which situations EFL teachers felt anxiety while teaching the target language. The analysis of the data resulted in 5 categories that can be sources of anxiety for EFL teachers while teaching the target language. Among these categories were making mistakes, fear of failure, and using the native language.